SABR-BRIDGE: Stereotactic ABlative Radiotherapy Before Resection to AvoId Delay for Early-Stage LunG Cancer or OligomEts During the COVID-19 Pandemic - Kidane, Biniam; Spicer, Jonathan; Kim, Julian O.; Fiset, Pierre-Olivier; Abdulkarim, Bassam; Malthaner, Richard; Palma, David (Frontiers in Oncology, 2020)
Surgical resection is the standard-of-care approach for early-stage non-small cell lung cancer (NSCLC). Surgery is also considered an acceptable standard infit patients with oligometastatic lesions in the lungs. The COVID-19 pandemic has led to worldwide issues with access to operating room time, with patients and physicians facing uncertainty as to when surgical resection will be available, with likely delays of months. Further compounding this are concerns about increased risks of respiratory complications with lung cancer surgery during active phases of the pandemic. In this setting, many thoracic oncology teams are embracing a paradigm where stereotactic ablative radiotherapy (SABR) is used as a bridge, to provide radical-intent treatment based on a combination of immediate SABR followed by planned surgery in 3–6 months. This pragmatic approach to treatment has been named SABR-BRIDGE (Stereotactic ABlative Radiotherapy Before Resection to avoId Delay for early-stage lunG cancer or oligomEts). This term has also been applied to the pragmatic study of the outcomes of this approach. In this paper, we discuss the standards of care in treatment of early-stage (NSCLC) and pulmonary oligometastases, the impetus for the SABR-BRIDGE approach, and the controversies surrounding assessment of pathological response to neo-adjuvant radiation therapy.